Non-Myeloid Cells are Major Contributors to Innate Immune Responses via Production of Monocyte Chemoattractant Protein-1/CCL2 - Yoshimura, Teizo; Galligan, Carole; Takahashi, Munehisa; Chen, Keqiang; Liu, Mingyong; Tessarollo, Lino; Wang, Ji Ming (Frontiers in Immunology, 2014)
Monocyte chemoattractant protein-1 (MCP-1)/CCL2 is a chemokine regulating the recruitment of monocytes into sites of inflammation and cancer. MCP-1 can be produced by a variety of cell types, such as macrophages, neutrophils, fibroblasts, endothelial cells and epithelial cells. Notably, macrophages produce high levels of MCP-1 in response to proinflammatory stimuli in vitro, leading to the hypothesis that macrophages are the major source of MCP-1 during inflammatory responses in vivo. In stark contrast to the hypothesis, however, there was no significant reduction in MCP-1 protein or the number of infiltrating macrophages in the peritoneal inflammatory exudates of myeloid cell-specific MCP-1-deficient mice in response to i.p injection of thioglycollate or zymosan A. Furthermore, injection of LPS into skin air pouch also had no effect on local MCP-1 production in myeloid-specific MCP-1-deficient mice. Finally, myeloid-specific MCP-1-deficiency did not reduce MCP-1 mRNA expression or macrophage infiltration in LPS-induced lung injury. These results indicate that non-myeloid cells, in response to a variety of stimulants, play a previously unappreciated role in innate immune responses as the primary source of MCP-1.